The Victimized Personas in Jean Rhys’s Wide Sargasso Sea and Charlotte Bronte’s Jane Eyre, Feminism Perspectives - Hayder M. Saadan M. Ridha AL-Hasani (RIRAI Publisher, 2023)
The Wide Sargasso Sea - (1966). After years of contemplating Charlotte Bronte's Creole madwoman Bertha Mason, Jean Rhys set out to give voice to what is mute in Bronte’s Jane Eyre. Rhys lets Antoinette narrate her tale, revealing the